Alien hand sign in association with Alzheimer's histopathology. Issue 9 (September 1993) - Ball, J A; Lantos, P L; Jackson, M; Marsden, C D; Scadding, J W; Rossor, M N
Abstract : A 68 year old man is described with an alien left hand, cortical myoclonus, bilateral parietal lobe dysfunction and memory impairment but preserved language skills. The clinical diagnosis was of corticobasal degeneration but at necropsy, four years after the onset of symptoms, the pathology was of Alzheimer's disease together with some scattered chromatolytic pale neurons in the cerebral cortex. The alien hand sign has not previously been described in Alzheimer's dementia and is an illustration of the clinical heterogeneity that may occur in association with Alzheimer histopathology.